How structure & board composition influence the financial performance of farm credit associations - Ramsey, Benjamin Hugh (My University, 2026)
The Farm Credit System (FCS) is a nationwide network of fifty-five borrower-owned financial cooperative associations playing a critical role in providing credit to U.S. agriculture and rural communities. Despite the system’s size and economic importance, there has been limited empirical research examining how governance structures influence the financial performance of Farm Credit associations. This study addresses that gap by analyzing the relationship between governance structure, board choices and financial performance across U.S. Farm Credit associations. Impact on financial performance, as measured by the return on equity, is the focus of this thesis. Using panel data from Farm Credit Administration (FCA) association annual reports covering the period from 2015 through 2024, this research evaluates governance variables including board size, female board representation, board compensation, chief executive officer tenure, member allocation of earnings, and senior leadership structure. Also, bank capital structure characteristics evaluated are characteristics known to impact performance such as size (e.g., assets), policy (e.g., capital ratio), financial structure (e.g., debt-to-asset), and cost (e.g., net interest rate margin and loss ratio). The dataset includes thirty-seven associations, including five of the seven associations affiliated with AgVantis, Inc. This distinction allows for examination of whether shared technology and service platforms influence governance effectiveness and financial outcomes in the AgVantis shared services consortium. Results indicate that financial structure and operational efficiency are the primary determinants of return on equity across Farm Credit associations. Net interest margin and loss ratio demonstrates the strongest and most consistent relationships with performance, while permanent capital ratio and leverage also contribute positively to several specifications. Governance variables exhibit more conditional effects. Senior leadership team size is positively associated with financial performance, and board size is negatively associated with return on equity among non-AgVantis associations. However, CEO tenure, female board representation, and board compensation do not consistently demonstrate statistically significant relationships. AgVantis affiliation appears more closely associated with reduced dispersion in performance outcomes than with higher average profitability. These findings suggest that governance influences financial outcomes indirectly through strategic and operational channels rather than as a standalone driver of profitability. The study contributes empirical evidence to cooperative governance research and provides practical insights for Farm Credit association boards, borrower-owners, and regulators seeking to sustain financial strength and long-term member value within the Farm Credit System.
Keywords: Governance; Board; Composition; AgVantis; Farm credit